An empirical study in brand image factors that influence students behaviour in Universiti Utara Malaysia - Fadli, Othman (2017)
The purpose of this study is to examine student behaviour towards brand image of Universiti Utara Malaysia (UUM) after awarded accreditation. In this study, the dimensions of brand image represented by brand personality and brand identity. Meanwhile, the dimensions of student behaviour represented by the factor satisfaction, expectation, performance and thought about study time. Respondent of this study are UUM student which are undergraduate and postgraduate students. The total of 379 questionnaires outcomes, has been analyse by using SPSS software version 24. Descriptive analysis, factor analysis, reliability analysis, Person's correlation analysis and multiple regression analysis has been used to answers research question and to achieve the research objective in this study. Result of this study shows that to achieve student's satisfaction and expectation in their behaviour, the dimension of brand image which are excitement, sincerity, sophistication, competence, ruggedness and identity caused effect against that relationship. Through the correlation test, the study found that there are positive significant relationship between the dimensions of brand image toward student behaviour. Meanwhile, according to multiple regression test, the result shows that the sincerity, competence and identity dimension became the major factor influence the student behaviour. Therefore, the university management should strengthen their brand image through these elements. Through multiple regression test also were resulted the excitement, sophistication and ruggedness dimension not have a significant relatio nship towards student behaviour. This shows that the university management could cut cost by not emphasize their brand image by excitement, sophistication and ruggedness dimensi on because these dimensions were not suitable for a university. However, the university would innovatively using the dimensions for influencing student behaviour. This study can be used by university management in improving their brand image to influence the student behaviour in future.